INCOME ANALYSIS OF POOR HOUSEHOLDS DURING COVID-19 PANDEMIC IN THE COASTAL AREA OF SOUTH SULAWESI - Nursini Nursini; Mardiana E. Fachry; Sri Undai Nurbayani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
The policy of limiting population mobility during the Covid-19 pandemic caused a slow economic turnaround. The economic slowdown has had an impact on the economic conditions of the poor, especially in coastal areas. This research aimed to analyze the income of poor households during the co-19 pandemic and analyze the effect of the large-scale social restriction (PSBB) policy and cash social assistance on poor household income. This study used a survey method in Makassar City and Pangkep Regency. Determination of the location used stratified random sampling. Unit of analysis of this research was the head of a poor household whose source of income is more dependent on fisheries and marine resources. This study used primary data and secondary data. Primary data was obtained from in-depth interviews with respondents and secondary data was obtained from the publication of the Central Bureau of Statistics (BPS). The data were analyzed using a statistical-descriptive model and multiple regression. This study found that the average income of respondents during the Covid-19 pandemic decreased by 14.5%. The PSBB policy variable significantly reduced the income of poor households in the study locations, but the cash social assistance variable did not significantly affect income because the amount was quite low and the value of cash social assistance received by poor households was uneven. To encourage poor households in coastal areas to get out of poverty problems.